No. 3x plus 2x = 5x. 3x multiplied by 2x = 6x²
3x-6x
2x - 6x + 3x = -412x - 3x = -41-1x = -41x = 41
There's no question there.3x + 6x - 2x is the same thing as 7x , and that's all there is to say about it.
Working from left to right:2x+x=3x3x-6x= -3x
No. 3x plus 2x = 5x. 3x multiplied by 2x = 6x²
3x-6x
2x - 6x + 3x = -412x - 3x = -41-1x = -41x = 41
There's no question there.3x + 6x - 2x is the same thing as 7x , and that's all there is to say about it.
2x+x+5+3x-6=6x-1
Working from left to right:2x+x=3x3x-6x= -3x
6x2 + 10x = 2x*(3x + 5)
3x(2x + 1)
2x-3x = -1
It is an expression that can be simplified to 4x
(3x + 2)(2x + 3)
-3x + 10x = 7x3x + 3x = 6x